Nurse Experience in Making Inter-Island Referrals for Emergency Patients: A Phenomenological Study - Setiyono Setiyono; Kumboyono Kumboyono; Suryanto Suryanto (Universitas Aisyah Pringsewu, 2023)
Making referrals for emergency patients is an activity that a nurse must do in remote areas. Referrals with trips that must pass by land and sea that take a long time will definitely encounter many obstacles and hindrances. Unpredictable obstacles experienced by a nurse in making referrals include accidents, port closures, and tidal waves. This study aimed to explore the experiences of nurses in making inter-island emergency referrals. This study is an interpretive qualitative research of phenomenology. The sampling technique used purposive sampling with criteria for nurses who had made inter-island emergency referrals. The participants were 25 nurses, with saturated data on the 14th participant. The process of collecting data was in-depth interviews until no new or saturated answers were found. From the results of the study, there were 3 themes, namely nurses' feelings (sad, happy, dejected, anxious, irritated, angry), obstacles (preparation, process, handover), and expectations (means, honorarium, energy, ease of transfer). Therefore, in the referral process, competent nurses, adequate facilities and infrastructure during trips, and the ability to communicate with various parties to ensure a smooth referral process must be prepared.